Pengaruh Pemberian Infusa Daun Kersen (Muntingia calabura L.) sebagai Disinfektan Alami Terhadap Penurunan Jumlah Bakteri dan Zona Hambat Pada Mesin Tetas Telur Itik - Vira Ajrina; Ellin Harlia; Yuli Astuti Hidayati (Unpad Press, 2021)
Cherry leaves are an alternative material that can be used as a natural disinfectant because they contain active com-pounds in the form of flavonoids, saponins, and tannins which can work as antibacterial compounds in duck egg hatching machines. The purpose of this study was to determine the effect of cherry leaf infusion and the most effective concentration level on the ability to reduce the number of bacteria and inhibit bac-teria in duck egg hatching machines. This research was conduc-ted experimentally using a Completely Randomized Design (CRD) and continued with the Tukey test with three treatments, namely P1 (50% concentration), P2 (75% concentration), and P3 (100% concentration) and six replications. The observed varia-bles were the decrease in the number of bacteria, inhibition zone of bacilli bacteria and inhibition zone of bacteria coccus in the duck egg hatching machine. The results showed that cherry leaf infusion had the same effect (P>0.05) on decreasing the number of bacteria and showed a different effect (P<0.05) on the inhibi-tion zone of gram positive and gram negative bacilli but had no effect on the inhibition zone gram negative and positive cocci bacteria, and cherry leaf infusion with a concentration of 75% produced the most effective inhibition zone for decreasing the number of bacteria and the ability to inhibit bacteria.